Silenced voices : reclaiming memories from the Guatemalan genocide - Leon, Pablo (Harper Alley, an imprint of HarperCollins Publishers, 2025)
Langley Park, Maryland, 2013. Brothers José and Charlie know very little about their mother's life in Guatemala, until José grows curious about the ongoing genocide trial of Efrain Rios Montt. At first his mother, Clara, shuts his questions down. But as the trial progresses, she begins to open up to her sons about a time in her life that she's left buried for years. Petén, Guatemala, 1982. Sisters Clara and Elena hear about the armed conflict every day, but the violence somehow seems far away from their small village. But the day the fight comes to their doorstep, the sisters are separated and are forced to flee through the mountains, leaving them to wonder...Have their paths diverged forever?